Pelanggaran Indikasi Geografis ditinjau dari Aspek Perlindungan Konsumen - Yoan Nursari Simanjuntak (Perspektif Hukum, 2023)
It is very important for Indonesia to provide protection for potential Geographical Indications in order to maintain fair business competition; consumer protection; protection of Micro, Small and Medium Enterprises; and domestic industry. Geographical indications, which are communal intellectual property rights, become an economic potential for the region or community group that proposes them. The protection of Geographical Indications will not only provide welfare benefits for the rights owners but will also constitute acknowledgment of the rights of end consumers who utilize products with said Geographical Indication rights. The regulation regarding violations of the rights of Geographical Indications contains protection for consumer rights and the obligations of producers. The study was carried out through normative juridical methods through statutory and conceptual approaches using legal materials, both primary, secondary and tertiary. Henceforth, the analysis is carried out deductively.